KREATIFITAS MAHASISWA DALAM PEMBELAJARAN MEMBATIK MENGGUNAKAN MEDIA LILIN DINGIN - Poppy Indriyanti; Dyan Indah Purnama Sari (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to: Describe the creativity of students in learning batik using cold wax media.Â This study uses a qualitative method. To collect data, researchers used interview techniques, direct field observation, documentation. The data analysis technique uses the Miles and Huberman methods, namely data editor, data presentation, verification. While the validity test of the data includes the test of internal validity (credibility), transferability testing, dependability testing and confirmation testing.Â The results of the study show that (1). Students' creativity in learning batik using cold wax media, the material is slightly different from the one given at the beginning of the discussion of the material needed, students make cold wax using starch because starch binds the cloth faster when applying to Mori cloth. (2). The making of motive patterns is very diverse, with a compact theme about the motives of the area ofÂ origin of each student, so as to make students aware of cultural heritage and can challenge local wisdom. (3) Using used bottles from cooking vinegar. (5) making a tutorial book where the book is material in the form of theory and practice into a book in which there are steps in making art that they have studied for one semester. From this assignment, the students showed their creativity again through the compilation of tutorials on how to use cold wax with great interest so that they could later use the book again when they went directly to the job to become elementary school teachers.